Encapsulating a Hydrophilic Chemotherapeutic into Rod-like Nanoparticles of a Genetically Encoded Asymmetric Triblock Polypeptide Improves its Efficacy - Bhattacharyya, Jayanta (Adv Funct Mater, 2017)
Encapsulating hydrophilic chemotherapeutics into the core of polymeric nanoparticles can improve their therapeutic efficacy by increasing their plasma half-life, tumor accumulation and intracellular uptake, and by protecting them from premature degradation. To achieve these goals, we designed a recombinant asymmetric triblock polypeptide (ATBP) that self-assembles into rod-shaped nanoparticles, and which can be used to conjugate diverse hydrophilic molecules, including chemotherapeutics, into their core. These ATBPs consist of three segments: a biodegradable elastin-like polypeptide, a hydrophobic Tyrosine-rich segment, and a short Cysteine-rich segment, that spontaneously self-assemble into rod-shaped micelles. Covalent conjugation of a structurally diverse set of hydrophilic small molecules, including a hydrophilic chemotherapeutic —gemcitabine— to the Cysteine residues also leads to formation of nanoparticles over a range of ATBP concentrations. Gemcitabine-loaded ATBP nanoparticles have significantly better tumor regression compared to free drug in a murine cancer model. This simple strategy of encapsulation of hydrophilic small molecules by conjugation to an ATBP can be used to effectively deliver a range of water-soluble drugs and imaging agents in vivo.